Adult T-cell leukemia/lymphoma: report of two cases Leucemia/linfoma de células T do adulto: relato de dois casos - Ricardo Aparecido Olivo; Fabrício Frederico Mendes Martins; Sheila Soares; Helio Moraes-Souza (Revista da Sociedade Brasileira de Medicina Tropical, 2008)
Adult T-cell leukemia/lymphoma is a lymphoproliferative disorder of mature T lymphocytes associated with infection with human T-cell lymphotrophic virus type I (HTLV-I). Adult T-cell leukemia/lymphoma is characterized by clinical and laboratory polymorphism that allows it to be classified into four distinct subgroups: smoldering, chronic, acute and lymphomatous types. We present here two cases of adult T-cell leukemia/lymphoma, respectively in the acute and lymphomatous forms of the disease. Case 1 was a 35-year-old woman who presented abdominal distension accompanied by hepatosplenomegaly, adenomegaly, skin lesions, positivity for anti-HTLV-I antibodies and leukocytosis with the presence of flower cells. Case 2 was a 38-year-old man who was admitted with generalized lymphadenomegaly, positivity for anti-HTLV-I antibodies, hypercalcemia and osteolytic lesions. In this paper, we correlate the clinical-laboratory findings of these two cases with data in the literature. A leucemia/linfoma de células T do adulto é um distúrbio linfoproliferativo de linfócitos T maduros associado à infecção pelo vírus linfotrópico de células T humanas tipo I (HTLV-I). A leucemia/linfoma de células T do adulto tem polimorfismo clínico e laboratorial, que a classifica em quatro subgrupos distintos entre si: smoldering, crônica, aguda e linfomatosa. Apresentamos neste artigo, dois casos de leucemia/linfoma de células T do adulto, respectivamente, nas formas aguda e linfomatosa da doença. O caso 1: uma paciente de 35 anos apresentava distensão abdominal com hepato-esplenomegalia, adenomegalia, lesões cutâneas, anticorpos anti-HTLV-I positivo e leucocitose com presença de flower cell. O caso 2: homem de 38 anos, internado com linfadenomegalia generalizada, anticorpos anti-HTLV-I positivo, hipercalcemia e lesões osteolíticas. Neste artigo correlacionamos os achados clínicos e laboratoriais destes dois casos com dados da literatura.